Survey of faculty development in four Israeli medical schools: clinical faculty development is inadequate and clinical teaching is undervalued in Israeli faculties of medicine - Simon Nothman; Michael Kaffman; Rachel Nave; Moshe Y. Flugelman (Israel Journal of Health Policy Research, 2021)
Abstract Background Teaching medical students is a central part of being a doctor, and is essential for the training of the next generation of physicians and for maintaining the quality of medicine. Our research reviews the training that physicians in Israel receive as teachers of clinical clerkships, and their thoughts regarding teaching students. The importance of faculty development cannot be overstated, for securing quality medicine and physician empowerment. Methods This study was based on a survey conducted among physicians teaching at Israeli medical schools. The survey was conducted using an online questionnaire sent to clinical teachers according to lists received from the teaching units of the faculties, department heads, and other clinical teachers. Participation in the study was anonymous. Findings Of 433 invited physicians, 245 (56%) from three departments (internal medicine, paediatrics, obstetrics and gynaecology) of four faculties of medicine in Israel, out of five total, completed the questionnaire. Only 35% of the physicians reported having received training for their role as teachers, most of these participated in a short course of up to 2 days. There were significant differences between the Technion and the other schools. Technion teachers without academic appointment had higher rates of pedagogic training. The same was true in regard to Technion teachers, either residents or young specialist. Significant gaps were reported between the content covered in the training and the topics the doctors felt they would want to learn. The clinicians who participated in the survey expressed that clinical teaching was less valued and more poorly remunerated than research, and that improved compensation and perceived appreciation would likely improve the quality of clinical teaching. Conclusions Of the one-third of the physicians surveyed who had received some training in clinical teaching, the training was perceived as inadequate and not aligned with their needs. There was a significant difference in rates of pedagogic training between the Technion and other medical schools. In addition, most clinical teachers surveyed felt that teaching students is inadequately valued. Due to its focus on just three disciplines, and higher relative number participants from the Technion faculty of medicine, our survey may not fully represent the activities of the faculties of medicine in Israel. Nevertheless, given the importance of clinical teaching of medical students, our findings argue for increasing faculty development and educational training of physicians in clinical settings, for recognizing the importance of teaching in academic and professional promotion processes.